SIA "SANO" ieiešanas stratēģija Somijas energoresursu uzskaites tirgū. - Lapinska, Marta (Latvijas Universitāte, 2018)
Bakalaura darba tēma ir SIA “SANO” ieiešanas stratēģija Somijas energoresursu uzskaites tirgū. Bakalaura darba mērķis ir pamatojoties uz Somijas energoresursu tirgu, SIA “SANO” uzņēmuma darbību, kā arī dažādu uzņēmumu pieredzi un ekspertu viedokļiem par Somijas tirgu analīzi noteikt piemērotāku ieiešanas stratēģiju SIA “SANO” Somijas energoresursu tirgū un izstrādāt priekšlikumus, lai attiecīgā stratēģija tiktu veiksmīgi sasniegta. Pētījuma rezultāti liecina, ka uzņēmumam ir iespējas ieiet Somijas energoresursu uzskaites tirgū, jo ir izpildīti priekšnosacījumi veiksmīgam eksportam: ir pietiekami liels vadības zināšanu līmenis, uzņēmums ir konkurētspējīgs, ir brīva ražošanas jauda, ko nav iespējams realizēt vietējā tirgū, un ir pieprasījums pēc pakalpojuma Somijas tirgū. Bakalaura darba izstrādē ir izmantoti 86 informācijas avoti, tā apjoms ir 77 lappuses. Diplomdarbā ir izmantoti 20 attēli, 9 tabulas un 2 pielikumi. Atslēgvārdi: starptautiskā uzņēmuma attīstība, eksports, tirgū ieiešanas stratēģijas, SIA SANO, Somijas energoresursu uzskates tirgus, viedie skaitītāji, uzņēmuma pārstāvju, eksperta intervijas.

Theme of the thesis is SIA “SANO” strategy for entering in Finland energy resource meter market. The aim of the thesis is to determine the best possible market entering strategy of SIA “SANO”, based on Finland energy resource market, SIA “SANO” current experience, the experience of other companies and expert opinions. The aim also includes defining proposals for achieving the strategy. Research results show that SIA “SANO” has possibilities to enter Finland’s energy resource market because all the prerequisites for successful export have been fulfilled – The knowledge level of the current management is high, company can be competitive, Finish market shows demand for this type of product and there is empty production capacity, that can not be fulfilled in local market. The results of the research indicate that the company has the opportunity to enter the Finnish energy resource market, as the preconditions for successful export are met: there is sufficient level of management knowledge, the company is competitive, there is free production capacity that is not realizable in the domestic market and there is demand for the service On the market in Finland. At the international level, not all companies are developing, although any product can be found on an export market or establish a branch abroad. There are several prerequisites for international development, which, according to the author, will not be possible expansion. One of the prerequisites is management knowledge and the decision to further develop the company beyond national boundaries. In the diploma paper are 86 sources of information, and 77 pages. Diploma paper includes 20 pictures, 9 tables and 2 annexes. Keywords: international business development, export, market entry strategies, SIA SANO, Finnish energy resource market, smart meters, business representatives, expert interviews
Entrance strategy of SANO Ltd. in the Finaland's energy consumer market.
Keywords: Vadībzinātne; Starptautiskā uzņēmuma attīstība; Tirgū ieešanas stratēģijas; Somija; Energoresursu uzskaites tirgus; Viedie skaitītāji